Effect of compost compactness, perforation in compost filled polybags and watering regime after casing on fruit body yield of White button mushroom, Agaricus bisporus - Ahlawat, O P; Manikandan, K (Mushroom Research, 2017)
The study presents the effect of compost compaction, perforation in compost filled polybags and the watering regime on the fruit body yield of the White button mushroom, A. bisporus. In four cultivation trials performed during different periods of three years, lowest time for first harvest (day post-casing) was recorded in compost compressed up to 3" along with perforation in compost filled polybags @ 30 holes of 0.5 cm dia./bag. In different compost compression treatments, the first harvest was earlier in bags with perforation in compost filled polybags compared to bags without perforation. Fruit body yield (kg/q compost) was also higher in bags with perforation in all levels of compost compression. However, it was highest in bags without any compression of compost but with perforation, followed by bags compressed up to 5" depth along with perforation. Although the average fruit body wt. was above 13 g in all the treatments but in majority of the cases it was higher in bags with perforation in compost filled polybags. The spent mushroom substrate from higher fruit body yielding treatments was found to have higher nitrogen content than in treatments which gave comparatively lower fruit body yield. Heavy watering on day 0, 4th and 7th, followed by routine spray of water gave higher fruit body yield than other watering regimes. Â